PsycEXTRA Dataset 1999
DOI: 10.1037/e448632006-001
|View full text |Cite
|
Sign up to set email alerts
|

1998 Department of Defense Survey of Health Related Behaviors Among Military Personnel

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 0 publications
5
71
0
Order By: Relevance
“…41 Another interesting finding is that almost half of all of the participants reported that they had attempted to quit smokeless tobacco use during past year. This is consistent with previous military reports by Bray and colleagues 14,18,[20][21] other sites were related to the requirement for multiple IRB reviews within the same service branches, significant differences in IRB protocol requirements, and differences in the requirements for informed consent documents.…”
supporting
confidence: 80%
“…41 Another interesting finding is that almost half of all of the participants reported that they had attempted to quit smokeless tobacco use during past year. This is consistent with previous military reports by Bray and colleagues 14,18,[20][21] other sites were related to the requirement for multiple IRB reviews within the same service branches, significant differences in IRB protocol requirements, and differences in the requirements for informed consent documents.…”
supporting
confidence: 80%
“…Previous research, however, indicates that "heavy drinking" rates are higher among 18-to 25-year-olds in the U.S. military than in the U.S. general population (Bray et al, 1999). It seems likely that the substance use patterns developed by young adults during military service could carry over into civilian life once members of the military retire or are discharged (Haddock et al, 1995;Talcott, Poston, and Haddock, 1998).…”
Section: Survey Nonresponse Bias Among Young Adults 173mentioning
confidence: 95%
“…While the program received moderate positive ratings from the majority of the sample, yoimger Marines, who are at greater risk for alcohol-related incidents and problems (Bray et al, 1999), rated the program as more useful, were more likely to recommend the program to others, and rated the program overall more positively than those Marines over the age of 25. This result may reflect findings from other studies on characteristics of computer users that show that younger people report more experience and acceptance of computer use (Vandelanotte & DeBourdeauhuij, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Participants reporting either any drinks or drinking on any number of days during the 30 days prior to the survey were counted as current drinkers. A heavy drinking category was computed for drinkers who reported 5 or more drinks per occasion at least once per week, a definition used in previous Department of Defense reports on alcohol use (Bray et al, 1999). Independent t tests were conducted to examine tiie bivariate associations between the four primary ratings of the program and demographic and alcohol use status variables.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation